The dynamic nature of HRM implementation: a structuration perspective - van Mierlo, Jorrit; Bondarouk, Tanya; Sanders, Karin (International journal of human resource management, 2018)
Over the past decades, scholars have dedicated substantial attention to the process of HRM implementation. Most progress has been made with debates on HRM system strength, roles of organisational actors in HRM implementation, and intended, actual and perceived HRM. In this paper, we challenge the current view on HRM implementation as being too static and one-directional. By building on structuration theory, we show that the process of HRM implementation is less straightforward than has been previously assumed. After their initial introduction, HRM practices evolve through turbulent developments. Furthermore, instead of neatly distributed roles following meticulously scheduled planning, HRM practices are influenced by various organisational actors. For successful implementation, HRM practices need to become inscribed into the interpretive schemes of organisational actors, resources have to be distributed, the HRM practice has to gain legitimacy. We develop a comprehensive framework that assists in understanding the process of HRM implementation.